The Velislav Bible, the finest picture-bible of the late middle ages: "Biblia depicta" as devotional, mnemonic and study tool - Panušková, Lenka ca. 20./21. Jh. (Central European Medieval Studies, 2018)
The Velislav Bible, one of the most beautiful medieval Bohemian manuscripts, is a bible imageé in which pictorial narrative dominates the written word, blending, at the same time, common biblical texts with a local legend about the patron of medieval Bohemia, St. Wenceslas. Deliberating about the role of this Bible, the essays collected in this monograph approach its manuscript in an interdisciplinary manner. By combining historical and textual analyses with the surveys of the Bible’s art and iconography, this first modern edition of the Velislav Bible and its tituli shows that it was used as a didactic tool in clerics’ education.